Negative electrode slurry for secondary battery and preparation method thereof

By crosslinking the negative electrode material of lithium-ion batteries with amino-terminated polyamic acid prepolymer solution with ternary anhydride to form a two-dimensional mesh-like surface structure, the crack problem caused by volume changes during the charging and discharging of the negative electrode material is solved, and the cycle stability of the battery and the first-time Coulomb efficiency are significantly improved.

CN115863528BActive Publication Date: 2025-04-04GUILIN ELECTRICAL EQUIP SCI RES INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211482086.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-04-04
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

The negative electrode materials of existing lithium-ion secondary batteries have cracks, powderization and peeling due to volume expansion and contraction during charging and discharging, resulting in capacity loss and battery failure, and the cycle stability and first-time Coulomb efficiency are not ideal.

Method used

A preparation method is adopted to prepare an amino-terminated polyamic acid prepolymer solution by using diamine and binary anhydride as raw materials, mix it with the negative electrode active material and conductive agent, and add ternary anhydride for cross-linking to form a two-dimensional mesh-like surface structure, which is fully coated on the surface of the negative electrode active material, forming a "cage"-shaped structure, which enhances adhesion and suppresses cracks caused by volume changes.

Benefits of technology

It significantly improves the cycle stability characteristics and first-time Coulomb efficiency of lithium-ion batteries, reduces the expansion effect of the negative electrode material, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a negative electrode slurry for a secondary battery and a preparation method thereof. The preparation method of the negative electrode slurry for a secondary battery comprises the following steps: 1) using diamine and dibasic anhydride as raw materials to prepare an amino-terminated polyamic acid prepolymer solution; 2) mixing the amino-terminated polyamic acid prepolymer solution with a negative electrode active material and a conductive agent, adding or not adding a polar solvent, and mixing to obtain a slurry precursor; 3) adding ternary anhydride to the slurry precursor, stirring and reacting, and obtaining the negative electrode slurry for the secondary battery; wherein the amount of ternary anhydride added is 0.01 to 1.0 mol% of the amount of diamine used in step 1). When the negative electrode slurry of the present invention is used to prepare a negative electrode for a secondary battery, the first efficiency and cycle stability of the secondary battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a secondary battery, and in particular to a negative electrode slurry for a secondary battery and a preparation method thereof. Background Art

[0002] Lithium ion secondary batteries, which are characterized by small size and large capacity, have been widely used as power sources for electronic devices such as mobile phones and laptop computers, and have contributed to improving the convenience of mobile IT equipment. In recent years, large-scale applications such as power sources for driving electric motorcycles and cars and storage batteries for smart grids have attracted attention. As the demand for lithium ion secondary batteries has increased and they have been used in various fields, batteries are required to have characteristics such as higher energy density, life characteristics that can withstand long-term use, and usability under a wide range of temperature conditions.

[0003] Among all battery structures, positive and negative electrode materials have the greatest impact on battery capacity. Among them, graphite is currently the most widely used negative electrode material, and its specific capacity is close to its theoretical value of 372mAh / g, while silicon-based negative electrode materials have a higher specific capacity of up to 4200mAh / g, and are considered to be the most likely material to replace graphite. However, silicon-based materials will undergo severe volume expansion and contraction during the battery charging and discharging process (up to about 400% expansion), making the material extremely prone to cracking, powdering and peeling, resulting in capacity loss and battery failure.

[0004] The use of carbon-coated silicon silicon-carbon composite negative electrode can reduce the volume effect of silicon. On this basis, the development of an adhesive that can bond with both copper foil and silicon-carbon materials at the same time can alleviate the volume expansion effect of the negative electrode material to a large extent, thereby improving the cycle stability of the silicon-carbon negative electrode and the battery life.

[0005] In order to alleviate the drawbacks of the volume expansion effect of silicon-containing negative electrodes during the charge and discharge process, the prior art proposes to use polyimide resin as a binder for negative electrode active materials. For example, the invention patent with publication number CN114805804A discloses a method for preparing a polyimide binder, comprising the following steps: (i) polycondensing a dibasic acid anhydride with a diamine containing a common diamine and a functional diamine in a polar solvent to obtain a linear polyamic acid solution, and then adding a polyamine to react to obtain a branched cross-linked polyamic acid solution; (ii) fully mixing and stirring the positive electrode active material or the negative electrode active material, the conductive agent, the branched cross-linked polyamic acid solution and the polar solvent to obtain an electrode slurry; (iii) uniformly coating the electrode slurry on the current collector, then drying and rolling, and finally heat treating to obtain the polyimide binder on the lithium ion battery pole piece. The invention points out that the use of functional diamines with strong polar groups (at least one of hydroxyl groups, carboxyl groups, sulfonic acid groups, trifluoromethyl groups, and cyano groups) makes the prepared polyimide adhesive have strong polarity, and the addition of polyamines makes the prepared polyimide adhesive have a branched cross-linked structure; the polyimide adhesive with strong polarity and branched cross-linked structure obtained by the addition of functional diamines and polyamines has a strong hydrogen bond effect and bonding effect with the active material, which greatly enhances the adhesion between the electrode material components and effectively ensures the integrity of the electrode components; at the same time, the formation of a uniform and continuous protective coating on the surface of the active material greatly improves the coating performance of the adhesive and effectively ensures the stability of the electrode-electrolyte interface. Specifically, when it is applied to the negative electrode, it has better adhesion than the ordinary PVDF system; and when it is applied to the positive electrode, the capacity retention rate of the lithium-ion battery after 100 cycles at 25°C is about 90%; for the negative electrode, there is no data recording that it effectively improves the battery properties (better capacity retention rate). In general, the improvement of the cycle stability of the polyimide resin binder is not ideal, and the first coulombic efficiency of the battery after being applied to lithium-ion secondary batteries is not recorded. On the other hand, the applicant found that the above invention adds polyamine before slurry mixing, which easily causes the system to gel when the addition amount is high, resulting in the polyamic acid solution being unusable. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a negative electrode slurry for a secondary battery and a preparation method thereof, which can effectively improve the first coulomb efficiency (first efficiency) and cycle stability of the secondary battery.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A method for preparing negative electrode slurry for a secondary battery comprises the following steps:

[0009] 1) using diamine and dibasic anhydride as raw materials to prepare an amino-terminated polyamic acid prepolymer solution;

[0010] 2) mixing the amino-terminated polyamic acid prepolymer solution with the negative electrode active material and the conductive agent, adding or not adding a polar solvent, and mixing evenly to obtain a slurry precursor;

[0011] 3) Adding ternary anhydride to the slurry precursor and stirring for reaction to obtain the negative electrode slurry for secondary battery; wherein the amount of ternary anhydride added is 0.01-1.0 mol% of the amount of diamine used in step 1).

[0012] The negative electrode slurry of the present invention forms a two-dimensional mesh surface structure that is fully coated on the surface of the negative electrode active material by adding ternary anhydride for cross-linking after slurry mixing. The polyamic acid molecular chains of the two-dimensional cross-linked mesh surface structure are coated on the micro-nano porous silicon powder or porous silicon-carbon composite active material body in a form similar to a whole plane network, forming a "cage" structure; on the other hand, the polyamic acid and / or polyimide molecular chains themselves are chemically bonded to the surface active groups of the silicon powder by covalent bonds, hydrogen bonds, etc. to form a strong adhesive force. The combined effect of the above two aspects effectively suppresses the influence of cracks or micronization caused by repeated volume expansion and contraction changes of silicon-based materials during the charging and discharging process, thereby greatly improving the cycle stability characteristics and first effect (first coulomb efficiency) of lithium-ion batteries.

[0013] In step 3) of the above preparation method, the ternary anhydride is preferably selected from one or a combination of two or more of mellitic acid trianhydride, hexaazatrimellitic acid trianhydride or benzo[G,H,I]perylene-1,2,4,5,10,11-hexacarboxylic acid trianhydride, and more preferably hexaazatrimellitic acid trianhydride containing an N-heterocyclic ring. Preferably, the ternary anhydride is first dissolved in a polar solvent and then added in the form of a solution.

[0014] The applicant found in the experiment that the control of the amount of ternary anhydride added is critical, which directly affects whether the resulting negative electrode slurry is gelled and the battery characteristics (such as the first effect and the inhibition of volume expansion effect) when applied to lithium-ion batteries. The applicant's test results show that when the amount of ternary anhydride added is controlled to 0.05-0.5 mol% of the amount of diamine used in step 1), the resulting negative electrode slurry can be applied to the negative electrode of a lithium-ion battery. Better first effect and cycle stability characteristics. In a more preferred embodiment, the amount of ternary anhydride added is controlled to be 0.05-0.1 mol% of the amount of diamine used in step 1).

[0015] In step 1) of the above preparation method, the diamine and dibasic anhydride are conventional aromatic diamine and aromatic dibasic anhydride, and the amino-terminated polyamic acid prepolymer solution is prepared by conventional methods (such as in-situ polymerization), such as placing the diamine and dibasic anhydride in a polar aprotic solvent and reacting them through polycondensation. The selection and amount of the polar aprotic solvent, the temperature and time of the polycondensation reaction, etc. are the same as those in the prior art. For example, the polar aprotic solvent may specifically be any one of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N-methylcaprolactam, hexamethylphosphoric triamide, 1,2-dimethoxyethane, bis(2-methoxyethyl) ether, 1,2-bis(2-methoxyethoxy)ethane, tetrahydrofuran, bis[2-(2-methoxyethoxy)ethyl] ether, 1,4-dioxane, dimethyl sulfoxide, dimethyl sulfone, diphenyl ether, cyclopentane, diphenyl sulfone, tetramethyl urea, m-cresol, phenol and γ-butyrolactone, or a combination of two or more thereof. Further preferred are N, N-dimethylacetamide, N, N-diethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone or γ-butyrolactone, and particularly preferred are N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone or γ-butyrolactone. The selection of other parameters is not described in detail here. In this step, based on the preparation of the amino-terminated polyamic acid prepolymer solution, the diamine is in excess relative to the dibasic anhydride, and their molar ratio is preferably 1: 0.94-0.99, and particularly preferably 1: 0.95-0.97. The applicant found in the experiment that the viscosity of the prepolymer solution system is more suitable at 2000-80000cp. If the viscosity of the prepolymer solution system is too large, gelation is easily formed when the ternary anhydride is added.

[0016] Further, it is preferred that the diamine is an asymmetric diamine, and it is preferred that the dianhydride is an asymmetric diamine, so that the first effect and cycle stability characteristics of the lithium ion battery can be further optimized. Specifically, the asymmetric diamine can be selected from 3,4'-diaminobenzanilide (3,4'-DABA), 3,4'-diaminodiphenyl ether (3,4'-ODA), metaphenylenediamine (m-PDA), 3,4'-diaminodiphenyl sulfone (3,4'-DDS), 3,4'-diaminobiphenyl (3,4'-DAB), 3,4'-diaminodiphenylmethane (3,4'-MDA), 3,4'-diaminodiphenyl disulfide and 3,4'-diaminodiphenyl sulfide, any one or a combination of two or more, further preferably 3,4'-DABA, 3,4'-ODA or 3,4'-diaminodiphenyl sulfide, particularly preferably 3,4'-DABA. The asymmetric structural dianhydride can be any one selected from 2,3,3',4'-biphenyltetracarboxylic dianhydride (α-BPDA), 2,3,3',4'-benzophenone tetracarboxylic dianhydride (2,3,3',4'-BTDA), 2,3,3',4'-diphenyl sulfone tetracarboxylic dianhydride (2,3,3',4'-DSDA), 2,3,3',4'-diphenyl sulfide tetracarboxylic dianhydride (2,3,3',4'-TDPA) and 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride (α-ODPA), or a combination of two or more thereof, more preferably 2,3,3',4'-DSDA or 2,3,3',4'-TDPA, and particularly preferably 2,3,3',4'-TDPA.

[0017] In step 2) of the above preparation method, the negative electrode active material and the conductive agent are conventionally selected in the prior art. The negative electrode active material is preferably a combination of one or more of carbon, silicon and silicon alloy, and is further preferably a porous silicon-carbon composite powder containing porous silicon powder or silicon alloy powder; the conductive agent is usually conductive carbon black. The ratio of the amino-terminated polyamic acid prepolymer solution, the negative electrode active material and the conductive agent is also the same as that in the prior art. In the present application, the weight ratio of the amino-terminated polyamic acid prepolymer solution, the negative electrode active material and the conductive agent is preferably 15-2:65-96:20-2, wherein the amino-terminated polyamic acid prepolymer solution is calculated based on the amount of solid components in the prepolymer solution.

[0018] The polar solvent involved in step 2) of the above preparation method is a conventional solvent used in the prior art for preparing negative electrode slurry, and can be specifically the same as the polar aprotic solvent used in the preparation of the polyamic acid prepolymer solution, preferably NMP and / or DMAc. The amount of polar solvent used in this step is to make the viscosity of the resulting slurry precursor meet the requirements of easy coating, and the viscosity of the resulting slurry precursor is usually controlled to be 2000-10000cp, preferably 4000-7000cp. When the viscosity of the amino-terminated polyamic acid prepolymer solution prepared in the early stage is relatively low, after adding the negative electrode active material and the conductive agent and stirring evenly, the viscosity of the system is just within the above-mentioned limited range, and no polar solvent needs to be added.

[0019] The present invention also includes negative electrode slurry for secondary battery prepared by the above method.

[0020] Compared with the prior art, the present invention is characterized in that:

[0021] 1. The present invention forms a two-dimensional mesh surface structure that is fully coated on the surface of the negative electrode active material by adding ternary anhydride for cross-linking in the later stage of slurry preparation. The polyamic acid molecular chains of the cross-linked mesh surface structure are coated on the micro-nano porous silicon powder or porous silicon-carbon composite active material body in a form similar to a whole plane network, forming a "cage" structure; on the other hand, the polyamic acid and / or polyimide molecular chains themselves are chemically bonded to the surface active groups of the silicon powder by covalent bonds, hydrogen bonds, etc. to form a strong adhesive force. The combined effect of the above two aspects effectively suppresses the influence of cracks or micronization caused by repeated volume expansion and contraction changes of silicon-based materials during the charging and discharging process, thereby greatly improving the cycle stability characteristics and first effect of lithium-ion batteries.

[0022] 2. Furthermore, the polyimide structure formed by the imidization reaction of the polyamic acid synthesized by the asymmetric structure monomer has a high degree of amorphous phase, which can improve the lithium ion conductivity in the lithium battery system, that is, the lithium ions can quickly migrate in the amorphous phase of the locally relaxed chain segments in the polyimide structure, so that the binder has good mechanical properties, high room temperature conductivity and a wide chemical stability window, etc., further optimizing the cycle stability, first efficiency and high rate characteristics of the lithium ion battery.

[0023] 3. The negative electrode slurry prepared with N-containing asymmetric diamine and N-containing heterocyclic group-containing ternary anhydride can further optimize the lithium battery properties (such as first effect, cycle stability, etc.).

[0024] 4. The negative electrode slurry of the present invention is used to prepare a negative electrode layer, which is further applied to a lithium-ion battery. The prepared battery has an initial coulombic efficiency of ≥90%, a capacity retention rate of ≥96% after 200 cycles, and a pole piece Z-direction (thickness direction) expansion rate of ≤56% before and after 200 cycles. DETAILED DESCRIPTION

[0025] In order to better explain the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments, but the embodiments of the present invention are not limited thereto.

[0026] Example 1

[0027] 1. Preparation of negative electrode slurry

[0028] 1) Under nitrogen atmosphere and room temperature, 36.447 g (0.182 mol) of aromatic diamine 4,4'-diaminodiphenyl ether (4,4'-ODA) was stirred and dissolved in 510 g of NMP, and then a total of 53.018 g (0.180 mol, added in 3 portions) of aromatic dibasic anhydride 3,3',3,4'-biphenyltetracarboxylic acid dianhydride (s-BPDA) (the molar ratio of diamine to dibasic anhydride was 1:0.99) was added, and stirred for 24 hours to obtain an amino-terminated polyamic acid prepolymer solution (the solid content of the obtained polyamic acid prepolymer solution was about 15%, and the total solid content was about 90 g);

[0029] 2) Take 135 g of the amino-terminated polyamic acid prepolymer solution obtained in step 1) (total solid content of 15 g), 650 g of negative electrode active material (520 g of graphite, nanoporous silicon powder (specific surface area of ​​about 58.196 m 2 / g, average mesopore diameter of about 26.9nm, the same below), 130g of graphite: nanoporous silicon powder = 8:2) and 20.0g of conductive agent (conductive carbon black), wherein active material: binder: conductive agent = 65:15:20 (weight ratio), are mixed evenly, 1400g of NMP is added, the obtained mixture is ground and blended to obtain a slurry precursor (viscosity is about 6920cp);

[0030] 3) Add 8.742 mg (0.031 mmol) of ternary anhydride mellitic acid trianhydride to the obtained slurry precursor (the amount of ternary anhydride added is equivalent to 0.01 mol% of the amount of diamine used in step 1)), stir and react for 6 hours to obtain the negative electrode slurry.

[0031] 2. Preparation of positive and negative electrodes of lithium batteries

[0032] 2.1 Negative electrode

[0033] The negative electrode slurry prepared in this embodiment was evenly coated on the copper foil, and the gap between the coating roller (scraper) was adjusted to control the thickness of the negative electrode slurry after curing to be 38 μm ± 2.0 μm. The copper foil evenly coated with the negative electrode slurry was placed in an oven, and heated at 80°C for 1 hour under the condition of nitrogen flow and oxygen concentration below 18 ppm, and then increased to 320°C at a rate of 3.0°C / min, and kept at 320°C for 2.0 hours to obtain a negative electrode sheet.

[0034] 2.2 Positive electrode

[0035] The active material ternary positive electrode (NCM523): polyvinylidene fluoride: conductive carbon black was stirred and mixed evenly in a weight ratio of 95:2:3, and the solvent NMP was added to adjust the system to an appropriate viscosity (6000±500cp), and the mixture was placed in a three-roll mill for 3 hours and dispersed at high speed for 2 hours to obtain a positive electrode slurry. The positive electrode slurry was coated on aluminum foil using a doctor blade, and the gap between the coating roller (scraper) was adjusted to control the thickness of the positive electrode slurry after curing to 110μm±3.0μm. The coated aluminum foil was placed in an oven and kept at 120°C for 2.2 hours under air circulation to obtain a positive electrode sheet.

[0036] 3. Preparation of Cells

[0037] In order to reduce the gap between the active materials, the above-mentioned lithium battery negative electrode sheet and positive electrode sheet are appropriately rolled using a roller press. The rolled negative electrode sheet and positive electrode sheet are cut into discs with a diameter of 14 mm using a punching machine. In an argon glove box (H2O < 0.01ppm O2 < 0.01ppm), CR2032 button batteries are assembled, and the negative electrode shell, negative electrode sheet, diaphragm, positive electrode sheet, nickel foam, spring sheet, and positive electrode shell are assembled in sequence. About 1mL of electrolyte is dripped at both ends of the diaphragm. The electrolyte is a mixed solution of 1.0mol / LLiPF6 dissolved in EC and DMC (EC:DMC=1:1, volume ratio). The assembled battery is placed in a sealing machine for packaging, and the packaging pressure is 75MPa. After standing for 24h, the corresponding electrochemical performance test is performed.

[0038] 4. Charge and discharge characteristics test

[0039] Each group of batteries manufactured by the above method was subjected to a cyclic charge and discharge characteristic test. The batteries were subjected to charge and discharge tests and cycle tests at 25°C. The experiment adopted a 0.2C current charge and discharge test with a voltage window of 0.005 to 1.5V. The amount of electricity flowing from the start of charging or discharging to the end was defined as the charge capacity or discharge capacity.

[0040] The charge and discharge efficiency of the battery was tested for the first time and after 200 cycles [charge and discharge efficiency = (discharge capacity / charge capacity)*100%).

[0041] The thickness of the negative electrode sheet in the scanning electron microscope cross-section of the battery before and after 200 cycles of charging and discharging with the adhesive was used as a reference, and the expansion rate of the negative electrode sheet was calculated based on the thickness of the active material of the electrode sheet before charging and the thickness of the active material of the electrode sheet after 200 cycles. 200 , and according to the calculation formula (thickness direction Z) expansion rate = (H 200 -H0) / H0*100% to calculate the pole piece expansion rate.

[0042] The test results are: the initial coulomb efficiency is about 90%, the capacity retention rate after 200 cycles is about 96%, and the expansion rate of the electrode in the Z direction (thickness direction) after 200 cycles is about 56%.

[0043] Comparative Example 1-1

[0044] The same as Example 1, the only difference is that when preparing the negative electrode slurry, step 3) is omitted, that is, the slurry precursor prepared in step 2) is used as the negative electrode slurry to prepare the negative electrode.

[0045] The test results are: the initial coulomb efficiency is about 76%, the capacity retention rate after 200 cycles is about 79%, and the expansion rate of the electrode in the Z direction (thickness direction) after 200 cycles is about 128%.

[0046] Comparative Example 1-2

[0047] The same as Example 1, the only difference is that when preparing the negative electrode slurry, the ternary anhydride is added before adding the negative electrode active material and the conductive agent. The specific operation is as follows:

[0048] 1) Same as step 1) of Example 1;

[0049] 2) 135 g of the amino-terminated polyamic acid prepolymer solution obtained in step 1) (total solid content of 15 g) was mixed with 8.742 mg (0.031 mmol) of ternary anhydride mellitic acid trianhydride (the amount of ternary anhydride added was equivalent to 0.01 mol% of the amount of diamine used in step 1) and stirred for reaction for 6 h;

[0050] 3) Add 650g of negative electrode active material (520g of graphite, nanoporous silicon powder (specific surface area of ​​about 58.196m 2 / g, the average mesopore size is about 26.9nm, the same below), 130g, graphite: nanoporous silicon powder = 8:2) and 20.0g conductive agent (conductive carbon black), wherein active material: binder: conductive agent = 65:15:20 (weight ratio), are mixed evenly, and then 1400g NMP is added, and the resulting mixture is ground and blended to obtain a negative electrode slurry.

[0051] The test results are: the initial coulomb efficiency is about 88%, the capacity retention rate after 200 cycles is about 93%, and the expansion rate of the electrode in the Z direction (thickness direction) after 200 cycles is about 95%.

[0052] Comparative Examples 1-3

[0053] The same as Example 1, except that when preparing the negative electrode slurry, the amount of ternary anhydride added in step 3) is equivalent to 1.05 mol% of the amount of diamine used in step 1).

[0054] The obtained negative electrode slurry has a gel point and cannot be normally coated and used, and then the negative electrode cannot be prepared, and the battery characteristics cannot be tested.

[0055] Example 2

[0056] The same as Example 1, except that the amount of mellitic acid trianhydride added in step 3) is changed to 0.875 g (3.035 mmol) (the amount of ternary anhydride added is equivalent to 1.0 mol% of the amount of diamine used in step 1)), and the stirring reaction time is changed to 8 hours.

[0057] The test results are: the initial coulombic efficiency is about 92%, the capacity retention rate after 200 cycles is about 97%, and the expansion rate of the electrode in the Z direction (thickness direction) after 200 cycles is about 55%.

[0058] Comparative Example 2-1

[0059] The same as Example 2, the only difference is that when preparing the negative electrode slurry, the ternary anhydride is added before adding the negative electrode active material and the conductive agent. The specific operation is as follows:

[0060] 1) Same as step 1) of Example 2;

[0061] 2) 135 g of the amino-terminated polyamic acid prepolymer solution obtained in step 1) (total solid content of 15 g) was mixed with 0.875 g (3.035 mmol) of ternary anhydride mellitic acid trianhydride (the amount of ternary anhydride added was equivalent to 1.0 mol% of the amount of diamine used in step 1) and stirred for reaction for 8 hours. The polyamic acid solution obtained in this step had a gel point and could not be used for the preparation of the negative electrode slurry in the next step.

[0062] Example 3

[0063] 1) Under nitrogen atmosphere and room temperature, 34.132 g (0.170 mol) of asymmetric diamine 3,4'-diaminodiphenyl ether (3,4'-ODA) was stirred and dissolved in 704 g of DMAc, and then a total of 53.621 g (0.164 mol, added once) of asymmetric dibasic anhydride 2,3,3',4'-diphenyl sulfide tetracarboxylic dianhydride (2,3,3',4'-TDPA) was added (the molar ratio of diamine to dibasic anhydride was 1:0.94), and the mixture was stirred and reacted for 12 h to obtain an amino-terminated polyamic acid prepolymer solution (the solid content of the obtained polyamic acid prepolymer solution was about 12%, and the total solid content was about 96 g);

[0064] 2) 84.0 g of the anhydride-terminated polyamic acid prepolymer solution obtained in step 1) (total solid content of 15.0 g), 80.0 g of negative electrode active material (40 g of graphite, 40 g of nanoporous silicon powder, graphite: nanoporous silicon powder = 5:5) and 10.0 g of conductive agent (conductive carbon black), wherein the active material: binder: conductive agent = 80:10:10 (weight ratio), are mixed evenly, and about 185 g of DMAc is added. The resulting mixture is ground and blended to obtain a slurry precursor (viscosity of about 4080 cp);

[0065] 3) Add 0.04 g (0.139 mmol) of ternary anhydride mellitic acid trianhydride to the obtained slurry precursor (the amount of ternary anhydride added is equivalent to 0.5 mol% of the amount of diamine used in step 1)), stir and react for 6 hours to obtain the negative electrode slurry.

[0066] The preparation of the positive and negative electrodes of the lithium battery, the preparation of the battery, and the charge and discharge characteristics test are the same as in Example 1.

[0067] The test results are: the initial coulomb efficiency is about 95%, the capacity retention rate after 200 cycles is about 98%, and the expansion rate of the electrode in the Z direction (thickness direction) after 200 cycles is about 52%.

[0068] Comparative Example 3-1

[0069] 1. Preparation of negative electrode slurry

[0070] 1) Under nitrogen atmosphere and room temperature, 63.399 g (0.293 mol) of asymmetric diamine 3,4'-diaminodiphenyl ether (3,4'-ODA) was stirred and dissolved in 840 g of DMAC, and then a total of 96.601 g (0.296 mol, added in 3 portions) of asymmetric dibasic anhydride 2,3,3',4'-diphenyl sulfide tetracarboxylic dianhydride (2,3,3',4'-TDPA) was added (the molar ratio of diamine to dibasic anhydride was 0.99:1), and the mixture was stirred and reacted for 24 hours to obtain a polyamic acid prepolymer solution terminated with anhydride groups (the solid content of the obtained polyamic acid prepolymer solution was about 16%, and the total solid content was about 160 g);

[0071] 2) 37.5 g of the anhydride-terminated polyamic acid prepolymer solution obtained in step 1) (total solid content of 6.0 g), 90.0 g of negative electrode active material (45 g of graphite, 45 g of nanoporous silicon powder, graphite: nanoporous silicon powder = 5:5) and 4.0 g of conductive agent (conductive carbon black), wherein the active material: binder: conductive agent = 90:6:4 (weight ratio), are mixed evenly, and about 150 g of NMP is added. The resulting mixture is ground and blended to obtain a slurry precursor (viscosity of about 10000 cp);

[0072] 3) 1,3,5-triaminobenzene (TAB) triamine (the amount of triamine is 0.1 mol% of the total molar amount of dibasic anhydride, diamine and triamine) was added to the obtained slurry precursor, and the reaction was stirred for 3 hours to obtain a negative electrode slurry.

[0073] The preparation of the positive and negative electrodes of the lithium battery, the preparation of the battery, and the charge and discharge characteristics test are the same as in Example 1.

[0074] The test results are: the initial coulomb efficiency is about 84%, the capacity retention rate after 200 cycles is about 88%, and the expansion rate of the electrode in the Z direction (thickness direction) after 200 cycles is about 89%.

[0075] Comparative Example 3-2

[0076] The same as comparative example 3, the only difference is that: when preparing the negative electrode slurry, the amount of triamine 1,3,5-triaminobenzene (TAB) added in step 3) is changed to 2 mol% of the total molar amount of dibasic anhydride, diamine and triamine, and the reaction is carried out. The obtained branched cross-linked polyamic acid solution gels and cannot be further used to prepare the negative electrode.

[0077] Example 4

[0078] 1. Preparation of negative electrode slurry

[0079] 1) Under nitrogen atmosphere and room temperature, 88.681 g (0.391 mol) of asymmetric diamine 3,4'-diaminobenzanilide (3,4'-DABA) was stirred and dissolved in 984 g of NMP, and then a total of 123.5 g (0.379 mol, added in 3 portions) of asymmetric diamine 2,3,3',4'-diphenyl sulfide tetracarboxylic dianhydride (2,3,3',4'-TDPA) was added (the molar ratio of diamine to diamine was 1:0.97), and the mixture was stirred and reacted for 22 hours to obtain an amino-terminated polyamic acid prepolymer solution (the solid content of the obtained polyamic acid prepolymer solution was about 18%, and the total solid content was about 216 g);

[0080] 2) 33.5 g of the anhydride-terminated polyamic acid prepolymer solution obtained in step 1) (total solid content of 6.0 g), 90.0 g of negative electrode active material (54 g of graphite, 36 g of nanoporous silicon powder, graphite: nanoporous silicon powder = 6:4) and 4.0 g of conductive agent (conductive carbon black), wherein the active material: binder: conductive agent = 90:6:4 (weight ratio), are mixed evenly, and about 120 g of NMP is added. The resulting mixture is ground and blended to obtain a slurry precursor (viscosity of about 10130 cp);

[0081] 3) Add 0.025 g (0.05 mmol) of the ternary anhydride hexaazatrimellitic acid ternary anhydride to the obtained slurry precursor (the amount of ternary anhydride added is equivalent to 0.5 mol% of the amount of diamine used in step 1)), stir and react for 4 hours to obtain the negative electrode slurry.

[0082] The preparation of the positive and negative electrodes of the lithium battery, the preparation of the battery, and the charge and discharge characteristics test are the same as in Example 1.

[0083] The test results are: the initial coulomb efficiency is about 96%, the capacity retention rate after 200 cycles is about 98%, and the expansion rate of the electrode in the Z direction (thickness direction) after 200 cycles is about 50%.

[0084] Example 5

[0085] The same as Example 4, except that: when preparing the negative electrode slurry, the amount of the ternary anhydride hexaazatrimellitic acid ternary anhydride added in step 3) is equivalent to 0.05 mol% of the amount of the diamine used in step 1).

[0086] The test results are: the initial coulomb efficiency is about 96%, the capacity retention rate after 200 cycles is about 98%, and the expansion rate of the electrode in the Z direction (thickness direction) after 200 cycles is about 51%.

[0087] Example 6

[0088] 1. Preparation of negative electrode slurry

[0089] 1) Under nitrogen atmosphere and room temperature, 53.778 g (0.269 mol) of asymmetric diamine 3,4'-diaminodiphenyl ether (3,4'-ODA) was stirred and dissolved in 850 g of NMP, and then a total of 91.412 g (0.256 mol, added once) of asymmetric diamine 2,3,3',4'-diphenylsulfone tetracarboxylic dianhydride (2,3,3',4'-DSDA) was added (the molar ratio of diamine to diamine was 1:0.95), and the mixture was stirred and reacted for 12 hours to obtain an amino-terminated polyamic acid prepolymer solution (the solid content of the obtained polyamic acid prepolymer solution was about 15%, and the total solid content was about 150 g);

[0090] 2) 40 g of the anhydride-terminated polyamic acid prepolymer solution obtained in step 1) (total solid content of 6.0 g), 88.0 g of negative electrode active material (44 g of graphite, 44 g of nanoporous silicon powder, graphite: nanoporous silicon powder = 5:5) and 6.0 g of conductive agent (conductive carbon black), wherein the active material: binder: conductive agent = 88:6:6 (weight ratio), are mixed evenly, and about 224 g of NMP is added. The resulting mixture is ground and blended to obtain a slurry precursor (viscosity of about 2926 cp);

[0091] 3) Add a DMF solution containing 0.039 g (0.086 mmol) of hexaazatrimellitic acid trianhydride to the obtained slurry precursor (formed by dissolving 0.039 g of hexaazatrimellitic acid trianhydride in 10 g of DMF, and the amount of hexaazatrimellitic acid trianhydride added is equivalent to 0.8 mol% of the amount of diamine used in step 1)), stir and react for 7.5 hours to obtain a negative electrode slurry.

[0092] The preparation of the positive and negative electrodes of the lithium battery, the preparation of the battery, and the charge and discharge characteristics test are the same as in Example 1.

[0093] The test results are: the initial coulomb efficiency is about 95%, the capacity retention rate after 200 cycles is about 98%, and the expansion rate of the electrode in the Z direction (thickness direction) after 200 cycles is about 52%.

Claims

1. A method for preparing a negative electrode slurry for a secondary battery, comprising the following steps: 1) using diamine and dibasic anhydride as raw materials to prepare an amino-terminated polyamic acid prepolymer solution; wherein, The diamine is an asymmetric diamine, specifically any one or a combination of two or more selected from 3,4'-diaminobenzanilide, 3,4'-diaminodiphenyl ether, m-phenylenediamine, 3,4'-diaminodiphenyl sulfone, 3,4'-diaminobiphenyl, 3,4'-diaminodiphenylmethane, 3,4'-diaminodiphenyl disulfide and 3,4'-diaminodiphenyl sulfide; The dibasic anhydride is an asymmetric structural dibasic anhydride, specifically any one or a combination of two or more selected from 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, 2,3,3',4'-diphenyl sulfone tetracarboxylic dianhydride, 2,3,3',4'-diphenyl sulfide tetracarboxylic dianhydride and 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride; The viscosity of the amino-terminated polyamic acid prepolymer solution is 2000-80000cp; 2) mixing the amino-terminated polyamic acid prepolymer solution with the negative electrode active material and the conductive agent, adding or not adding a polar solvent, and mixing evenly to obtain a slurry precursor; 3) adding a ternary anhydride to the slurry precursor and stirring the reaction to obtain the negative electrode slurry for the secondary battery; wherein the amount of the ternary anhydride added is 0.01-1.0 mol% of the amount of the diamine used in step 1); the ternary anhydride is one or a combination of two or more selected from mellitic acid trianhydride, hexaazatrimellitic acid trianhydride or benzo[G,H,I]perylene-1,2,4,5,10,11-hexacarboxylic acid trianhydride.

2. The preparation method according to claim 1, characterized in that: In step 3), the ternary anhydride is hexaazatrimellitic acid ternary anhydride.

3. The preparation method according to claim 1, characterized in that: In step 3), the amount of the ternary anhydride added is 0.05-0.5 mol% of the amount of the diamine used in step 1).

4. The preparation method according to claim 1, characterized in that: In step 3), the amount of the ternary anhydride added is 0.05-0.1 mol% of the amount of the diamine used in step 1).

5. A negative electrode slurry for a secondary battery prepared according to the method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Branched cross-linked polyamide acid solution, polyimide adhesive as well as preparation method and application of branched cross-linked polyamide acid solution and polyimide adhesive

    CN114805804A

  • Current collector for secondary battery, positive electrode for the secondary battery, negative electrode for the secondary battery, the secondary battery, and manufacturing method of them

    CN101116201A

  • Lithium secondary battery and method for manufacturing the same

    CN102201595A